2007
DOI: 10.1242/jcs.03360
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted mechanical stability of the dystrophin-glycoprotein complex causes severe muscular dystrophy in sarcospan transgenic mice

Abstract: The dystrophin-glycoprotein complex spans the muscle plasma membrane and provides a mechanical linkage between laminin in the extracellular matrix and actin in the intracellular cytoskeleton. Within the dystrophin-glycoprotein complex, the sarcoglycans and sarcospan constitute a subcomplex of transmembrane proteins that stabilize α-dystroglycan, a receptor for laminin and other components of the extracellular matrix. In order to elucidate the function of sarcospan, we generated transgenic mice that overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 70 publications
(94 reference statements)
1
23
0
Order By: Relevance
“…S1C). Previous work from our lab has shown that ten-fold transgenic expression of human SSPN in wild-type mice leads to a severe muscle phenotype that includes muscle degeneration, kyphosis and death at 6-10 weeks of age (27). By contrast, wild-type mice overexpressing mSSPN are healthy, breed well, exhibit no signs of muscle pathology, and appear to have a normal lifespan (the oldest transgenic carriers in our colony are currently over 2.5 years of age).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1C). Previous work from our lab has shown that ten-fold transgenic expression of human SSPN in wild-type mice leads to a severe muscle phenotype that includes muscle degeneration, kyphosis and death at 6-10 weeks of age (27). By contrast, wild-type mice overexpressing mSSPN are healthy, breed well, exhibit no signs of muscle pathology, and appear to have a normal lifespan (the oldest transgenic carriers in our colony are currently over 2.5 years of age).…”
Section: Resultsmentioning
confidence: 99%
“…SSPN-null mice were a generous gift from Dr. Kevin P. Campbell (University of Iowa Carver College of Medicine, Iowa City, IA) (37). Transgenic constructs were designed with the human skeletal actin promoter and VP1 intron upstream of the full-length mouse SSPN cDNA, as described previously (27,43). Transgenic mice were generated by microinjection of transgenic constructs into the pronucleus of fertilized single-cell embryos (C57BL/6J background, Transgenic Mouse Facility, University of California, Irvine), and four viable lines were recovered (Lines 28, 23, 32 and 15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An appropriate level of SSPN in the cell is also essential for the integrity of DGC. When overexpressed in mice by 10 fold, SSPN clusters the sarcoglycans into insoluble protein aggregates and causes the destabilization of α-dystroglycan (123). Microspan is an alternatively spliced product of the SSPN gene.…”
Section: Dystrophinmentioning
confidence: 99%
“…Notably, near-complete loss of α-dystroglycan expression has been reported in a patient with limb girdle muscular dystrophy (LGMD) who carried a dominant-negative mutation in Cav3, again suggesting that there is a functional relationship (Herrmann et al, 2000). A transgenic mouse overexpressing sarcospan, a protein component of the DGC, induces elevated levels of many DGC proteins and also Cav3 (Peter et al, 2007). Dystrophin localizes to caveolae-enriched areas in smooth muscle cells (North et al, 1993) and can be detected in Cav3 immunoprecipitates (Doyle et al, 2000).…”
Section: Cav1 Is Functionally Linked To the Extracellular Matrixmentioning
confidence: 99%